2013
DOI: 10.1016/j.scr.2013.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Generation of organized anterior foregut epithelia from pluripotent stem cells using small molecules

Abstract: Anterior foregut endoderm (AFE) gives rise to therapeutically relevant cell types in tissues such as the esophagus, salivary glands, lung, thymus, parathyroid and thyroid. Despite its importance, reports describing the generation of AFE from pluripotent stem cells (PSCs) by directed differentiation have mainly focused on the Nkx2.1(+) lung and thyroid lineages. Here, we describe a novel protocol to derive a subdomain of AFE, identified by expression of Pax9, from PSCs using small molecules and defined media co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 14 publications
1
25
0
Order By: Relevance
“…Green et al showed that dual inhibition of BMP‐ and Nodal/TGF‐β specified an AFE population. These results were recently reproduced by other reports although Kearns et al found that TGF‐β and BMP‐inhibition were not necessarily required. In contrast to that Hannan et al reported that activin A by Nodal/TGF‐β activation can direct endoderm into a SOX2‐positive AFE cell population that could be expanded into a foregut stem cell line capable of pancreatic and hepatic lineage commitment.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Green et al showed that dual inhibition of BMP‐ and Nodal/TGF‐β specified an AFE population. These results were recently reproduced by other reports although Kearns et al found that TGF‐β and BMP‐inhibition were not necessarily required. In contrast to that Hannan et al reported that activin A by Nodal/TGF‐β activation can direct endoderm into a SOX2‐positive AFE cell population that could be expanded into a foregut stem cell line capable of pancreatic and hepatic lineage commitment.…”
Section: Discussionsupporting
confidence: 83%
“…Several groups analyzed the mechanisms underlying the endoderm patterning into the foregut [10,11,[13][14][15][16] and hindgut [12,13,16]. Ameri et al [11] described that FGF-4 together with RA patterns the endoderm into PFE.…”
Section: Discussionmentioning
confidence: 99%
“…They are also progenitor r celsl for Type I Alveolar cells. Anterior Foregut Endoderm (AFE) : AFE gives rise to cell types such as esophagus, salivary glands, lung, thymus, parathyroid and thyroid glands. This tissue became the target for differentiation from iPSCs, and its heterogeneity could be an obstacle for trying to create lung‐specific cells AQP : aquaporin.…”
Section: Glossarymentioning
confidence: 99%
“…Three recent studies have reported efficient derivation of AFE progenitors from PSCs in vitro (Green et al, 2011;Brafman et al, 2013a;Kearns et al, 2013). Snoeck and colleagues demonstrated that inhibition of BMP4 and TGF-b signaling at the DE stage of hES or iPS cell directed differentiation leads to AFE derivation as witnessed by the reduced expression of hepatic and intestinal markers and the up-regulation of anterior markers such as SOX2, TBX1, NKX2-5 and PAX9 (Green et al, 2011).…”
Section: Anterior Foregut Progenitorsmentioning
confidence: 99%